2012
DOI: 10.1038/ijo.2012.191
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sphingolipids are biomarkers of metabolic syndrome in non-human primates maintained on a Western-style diet

Abstract: BACKGROUND The intake of a Western diet enriched in animal fat has been shown to be a major risk factor for Type 2 diabetes and obesity. Previous rodent studies have indicated that these conditions may be triggered by the accumulation of the sphingolipid ceramide in insulin-sensitive tissues. However, data are lacking in this regard from both humans and non-human primates. OBJECTIVE Here we have investigated the relationship between plasma ceramides and metabolic syndrome in Rhesus macaques fed a high-fat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 58 publications
(98 reference statements)
4
70
1
Order By: Relevance
“…Discrete serum ceramide profiles are rendered across the spectrum of diabetes development, creating speculation that ceramides not only mark but contribute to the disease process (8,17). Nevertheless, a paucity of interventional studies in humans has made this speculation difficult to confirm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrete serum ceramide profiles are rendered across the spectrum of diabetes development, creating speculation that ceramides not only mark but contribute to the disease process (8,17). Nevertheless, a paucity of interventional studies in humans has made this speculation difficult to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the idea that serum ceramides, specifically the C16:0 and C18:0 species, promote insulin resistance via activation of inflammatory cascades in muscle. Total and C18:0 serum dihydroceramide and ceramide have been shown to be associated with prediabetes and diabetes (8,15,28) as well as able to predict progression to type 2 diabetes in epidemiological cohorts (26,28). Recent data indicate that dihydroceramide is more than an inactive precursor to ceramide formation and is an important intra-and extracellular signal influencing sterol regulatory element gene transcription, autophagy, and mitochondrial function (3,32,36,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma b-hydroxypyruvate levels were positively correlated with plasma glucose levels in mice and b-hydroxypyruvate/D-serine ratios were higher in patients with T2DM compared with people with IGT in the study by Zhang et al (5). A previous study reported increased plasma serine (not necessarily D-serine) levels in diabetic nonhuman primates compared with nondiabetic control subjects (10). Thus, future studies should include the measurements of b-hydroxypyruvate, D-serine, and benzoate levels as well as b-hydroxypyruvate/D-serine ratio and DAO activity.…”
mentioning
confidence: 94%
“…Recently, alterations of the sphingolipid metabolism have been evidenced in obese and diabetic patients, with increased plasma levels of ceramide and sphingosine-1-phosphate, which are hypothesized to elicit an inflammatory condition [57,58]. In animal models of western diet, high in fats and fructose, the increased ceramide de novo synthesis has been reported, in relation with reduced insulin sensitivity [59,60]. In parallel, two very recent studies highlighted a possible role for diet-derived AGEs on this unbalance among sphingolipids intermediates through the action of the AGE-receptor RAGE [61,62].…”
Section: Interference On Sphingolipids Metabolismmentioning
confidence: 99%